Biosimilars in inflammatory bowel disease: copycats or genuine replacements? - Eri, Raj (Henry Stewart Talks, 2021)
Definition and characterization of biosimilars, Clinical development pathways, Biosimilars vs. generics, Biologics vs. biosimilars, Biosimilar processing, The global impact of biosimilars, IBD studies on biosimilars, Issues and concerns